Notifikasi Email Sebagai Pengingat Pengembalian Buku Pada Perpustakaan Berbasis Website Terintegrasi Dengan RFID Dan QR Code - Tiara Putri Amanda; Abdul Rakhman; Irma Salamah (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The library strives to maintain and improve efficiency and effectiveness in teaching and learning. Currently there are still many library services that use manual methods. Computerized service systems are able to streamline library services, so transactions such as searching, borrowing, returning and managing data can be done quickly and accurately. In this research, a website-based library service system is integrated with Radio Frequency Identification (RFID) as a library visitor identity card which can also be used when borrowing and returning books, and Quick Response Code (QR Code) is used as book identification. In this application the admin can process data, register books and members, borrow and return books, and view transaction reports. This application also provides e-mail notifications to resolve problems such as late returns to the loss of borrowed books. The notification automatically sends a message to the user to return the book on the last day of the loan. The existence of a service system in this website-based library application makes it easier for administrators in managing data, improving library services, and email notifications helps to remind the day of returning books.